Respuesta :

Answer:(3x-12)

Explanation:Rearranging the equation we get,

3x-12=y

which equals to

1/y=1/(3x-12)

Now,multiply both sides by x

x/y=x/(3x-12)

8x/2y=4x/y=4x/(3x-12)

Answer:

D)

Explanation:

First, let's rearrange the first equation in order to use the substitution method:

3x - y = 12

Add y to each side:

3x = 12 + y

Subtract 12 from both sides:

3x - 12 = y

y = 3x - 12

Then use substitution to solve for y:

[tex]\frac{8^x}{2^y}[/tex]

[tex]\frac{8^x}{2^(3x-12)}[/tex]

From my perspective, this is the farthest you can get until you can solve, so there is not enough information to solve this.